An integrated care pathway for menorrhagia across the primary–secondary interface: patients' experience, clinical outcomes, and service utilisation. Issue 2 (2nd April 2007) - Julian, Sophia; Naftalin, Nicholas J; Clark, Michael; Szczepura, Ala; Rashid, Aly; Baker, Richard; Taub, Nicholas; Habiba, Marwan
Abstract : Background: "Referral" characterises a significant area of interaction between primary and secondary care. Despite advantages, it can be inflexible, and may lead to duplication. Objective: To examine the outcomes of an integrated model that lends weight to general practitioner (GP)-led evidence based care. Design: A prospective, non-random comparison of two services: women attending the new (Bridges) pathway compared with those attending a consultant-led one-stop menstrual clinic (OSMC). Patients' views were examined using patient career diaries, health and clinical outcomes, and resource utilisation. Follow-up was for 8 months. Setting: A large teaching hospital and general practices within one primary care trust (PCT). Results: Between March 2002 and June 2004, 99 women in the Bridges pathway were compared with 94 women referred to the OSMC by GPs from non-participating PCTs. The patient career diary demonstrated a significant improvement in the Bridges group for patient information, fitting in at the point of arrangements made for the patient to attend hospital (ease of access) (p<0.001), choice of doctor (p = 0.020), waiting time for an appointment (p<0.001), and less "limbo" (patient experience of non-coordination between primary and secondary care) (p<0.001). At 8 months there were no significant differences between the two groups in surgical and medical treatment rates or in the use of GP clinic appointments. Significantly fewer (traditional) hospital outpatient appointments were made in the Bridges group than in the OSMC group (p<0.001). Conclusion: A general practice-led model of integrated care can significantly reduce outpatient attendance while improving patient experience, and maintaining the quality of care.